DAMPAK KEBIJAKAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL TERHADAP DAYA TARIK INVESTASI ASING DI PROVINSI RIAU TAHUN 2013-2016 - Annisha "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
With the enactment of regional autonomy by the Indonesian government, the riau provincial government established an institution that serves to minimize the process, the permit is always requested by the owners of capital / investors. The agency is the Integrated Licensing Service Agency and Capital Investment. This study aims to determine the policy of the institution, to know foreign investment in riau province, to know the impact of the policy of the institution to foreign investment in riau province. This research uses the perspectives of liberalism, this theory is pioneered by david ricardo & adam amith. The concept of this theory is based on the idea of market sovereignty in the economy. In this study the author uses the policy theory of Richard Snyder as a reference. The results of this study are positively impacting the economy in Riau province through incentive policies in the field of foreign investment including tax facilities and licensing facilities.Keywords : Impact, Bp2t Policy Attraction of, Foreign Investment, Riau Province